Carbon nanoparticles and nanostructures - Yang, Nianjun; Jiang, Xin; Pang, Dai-Wen (Switzerland Springer, 2016)
This book focuses on carbon dots and diamonds, briefly covering other nanocarbon structures such as nanohorns and nanofibers. In the first part, chemical synthesis of carbon dots, their optical properties and their applications for sensing, catalytic reactions, bio-imaging and drug delivery are presented. The second part of the book deals with the preparation and purification of diamond nanoparticles, their properties and surface chemistry as well as the applications of diamond nanoparticles for seeding, bio-imaging and drug delivery. In the third and last part of the book, other nanostructures such as carbon nanofibers and carbon nanohorns are presented, including their application in electrochemistry, biochemistry and energy.
From the Contents: Part I Diamond: Porous diamond -- Diamond nanowires -- Preparation and purification of diamond nanoparticles, seeding applications -- Part II Carbon Dots: Preparation of carbon dots -- Part III Other carbon nanostructures: Carbon nanofibers -- CVD growth and applications -- Carbon nanohorns.
Keywords: Nanostructured materials; Carbon